Mechanisms of Puerariae Lobatae Radix in regulating sebaceous gland secretion: insights from network pharmacology and experimental validation - Yijie, Du; Siqi, Zhao; Ruiyin, Huang; YuJing, Shi; Hong, Meng; Yinmao, Dong; Tao, Yang; Changyong, Luo (Frontiers in Pharmacology, 2024)
Objective: This research aims to explore how Puerariae Lobatae Radix regulates sebaceous gland secretion using network pharmacology, and validate its effects on important targets through animal studies.Methods: This study utilized UPLC-EQ-MS to analyze Puerariae Lobatae Radix extract and identify potential bioactive compounds. Predicted targets of these compounds were obtained from the Swiss Target Prediction database, while targets associated with sebaceous gland secretion were obtained from the GeneCards database. Common targets between the databases were identified and a protein-protein interaction (PPI) network was established using the STRING platform. The PPI network was further analyzed using Cytoscape software. Pathway enrichment analysis was performed using Reactome, and molecular docking experiments targeted pivotal pathway proteins. Animal experiments were then conducted to validate the regulatory effects of the primary active compounds of Puerariae Lobatae Radix on key pathway proteins.Results: This research identified 17 active compounds in Puerariae Lobatae Radix and Puerariae Lobatae Regulatds lipid metabolism 163 potential targets associated with the regulation of sebum secretion. Pathway enrichment analysis indicates that these targets may modulate lipid metabolism pathways through involvement in PPAR α, SREB, steroid metabolism, and arachidonic acid metabolism pathways. Molecular docking analysis demonstrates that puerarin and daidzein show favorable binding interactions with key targets in these pathways. Animal experiments demonstrated that the administration of Puerariae Lobatae Radix resulted in a significant reduction in the area of sebaceous gland patches compared to the control group. Histological analysis revealed notable alterations in the structure of sebaceous glands, including reductions in size, thickness, and density. Furthermore, the expression levels of TG, DHT, and IL-6 were significantly decreased in the Puerariae Lobatae Radix group (P<0.05), and immunoblotting indicated a significant decrease in the expression of PPARG and ACC1 (P<0.05).This study demonstrates that Puerariae Lobatae Radix can regulate skin lipid metabolism by targeting multiple pathways. The primary mechanism involves inhibiting sebaceous gland growth and reducing TG secretion by modulating the expression of PPARG and ACC1. Puerarin and Daidzein are identified as key bioactive compounds responsible for this regulatory effect. These findings highlight the therapeutic potential of Puerariae Lobatae Radix in addressing sebaceous gland-related conditions.